COMPARATIVE ANALYSIS OF THE EXPORT POTENTIAL OF THE REPUBLIC OF UZBEKISTAN WITHIN THE FRAMEWORK OF THE EAEU (American Journal of Interdisciplinary Research and Development, 2023)
The significance and function of export potential lie in its ability to serve as a crucial measure of competitiveness, affirming genuine competitive advantages. Additionally, it acts as an instrument for advancing national interests in the global economic landscape. This article provides a comparative analysis of Uzbekistan's export potential within the Eurasian Economic Union (EAEU). The article examines foreign trade relationships of Uzbekistan within this regional economic bloc.